Relevansi Pemikiran Ibnu Miskawaih Tentang Pendidikan Akhlak Dengan Pendidikan Moral Generasi Z - Dina Alfiatus Sholikhah; Jasminto (CV. KAMPUS AKADEMIK PUBLISING, 2026)
Moral education is education about the basics of morals and the virtues of temperament, character that must be owned and made a habit by the child from the time of analysis until he becomes a mukallaf. The problem discussed in this study is about the Relevance of Ibnu Miskawaih's Moral Education Thought on Moral Education with Generation Z Moral Education. Based on the above problems, this research has 3 objectives related to the research focus on the Relevance of Ibnu Miskawaih's Thought on Moral Education with Generation Z Moral Education. The research objectives are: 1) To describe Ibn Miskawaih's thoughts on moral education. 2) To describe the moral education of generation Z. 3) To describe the relevance of Ibnu Miskawaih's thoughts on morals with Z generation moral education. The type of research is library research. The research was conducted with a qualitative approach with descriptive methods. Data collection was carried out using written documentation and review techniques. In this analysis the author uses the content analysis method. Based on the results of the study found that: (1) Ibn Miskawaih's thought focuses on moral education based on the doctrine of the middle way (al- wasath) and the development of four virtues. (2) Generation Z moral education emphasizes character building with an emphasis on the values of integrity, empathy, responsibility, and tolerance. (3) The relevance of Ibn Miskawaih's thought to generation Z moral education lies in the similarity of basic values that are universal and flexible to be applied in various contexts of the times, including in the character building of today's digital generation.